Acute and Chronic Sleep Deprivation-Related Changes in N-methyl-D-aspartate Receptor-Nitric Oxide Signalling in the Rat Cerebral Cortex with Reference to Aging and Brain Lateralization - Kristofikova, Zdenka; Sirova, Jana; Klaschka, Jan; Ovsepian, Saak V (International journal of molecular sciences, 2019)
Aging and chronic sleep deprivation (SD) are well-recognized risk factors for Alzheimer's disease (AD), with N-methyl-D-aspartate receptor (NMDA) and downstream nitric oxide (NO) signalling implicated in the process. Herein, we investigate the impact of the age- and acute or chronic SD-dependent changes on the expression of NMDA receptor subunits (NR1, NR2A, and NR2B) and on the activities of NO synthase (NOS) isoforms in the cortex of Wistar rats, with reference to cerebral lateralization. In young adult controls, somewhat lateralized seasonal variations in neuronal and endothelial NOS have been observed. In aged rats, overall decreases in NR1, NR2A, and NR2B expression and reduction in neuronal and endothelial NOS activities were found. The age-dependent changes in NR1 and NR2B significantly correlated with neuronal NOS in both hemispheres. Changes evoked by chronic SD (dysfunction of endothelial NOS and the increasing role of NR2A) differed from those evoked by acute SD (increase in inducible NOS in the right side). Collectively, these results demonstrate age-dependent regulation of the level of NMDA receptor subunits and downstream NOS isoforms throughout the rat brain, which could be partly mimicked by SD. As described herein, age and SD alterations in the prevalence of NMDA receptors and NOS could contribute towards cognitive decline in the elderly, as well as in the pathobiology of AD and the neurodegenerative process.
Keywords: receptory N-methyl-D-aspartátu; Nitric Oxide Synthase; signální transdukce; Aging; Rats; Gene Expression Regulation; Rats, Wistar; mužské pohlaví; Signal Transduction; Receptors, N-Methyl-D-Aspartate; membránové glykoproteiny; Alzheimer Disease; spánková deprivace; acute and chronic sleep deprivation; brain lateralization; krysa rodu Rattus; věkové faktory; regulace genové exprese; cortex; stárnutí; Membrane Glycoproteins; synthasa oxidu dusnatého; mozková kůra; zvířata; oxid dusnatý; Nitric Oxide; Cerebral Cortex; NMDA receptor subunits; nitric oxide synthases; Sleep Deprivation; rizikové faktory; Age Factors; Alzheimerova nemoc; potkani Wistar; aging; Risk Factors; Male; Animals